2017
DOI: 10.1080/17470919.2017.1365761
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary physical exercise protects against behavioral and endocrine reactivity to social and environmental stressors in the prairie vole

Abstract: Physical activity can combat detrimental effects of stress. The current study examined the potential protective effects of exercise against a combination of social isolation and chronic mild stress (CMS) in a prairie vole model. Female voles were isolated for 4 weeks, with the addition of CMS during the final 2 weeks. Half of the voles were allowed access to a running wheel during this final 2 weeks, while the other half remained sedentary. Animals underwent behavioral tests to assess depressive- and anxiety-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 85 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…Exercise is also known to activate the HPA axis and increase circulating glucocorticoid levels (Gerber et al, 2013;Hill et al, 2008;Skoluda et al, 2012;Tremblay et al, 2004). However, under conditions of chronic stress, exercise mitigates glucocorticoid levels and reduces depression-and anxiety-like behaviors (Campeau et al, 2010;Grippo et al, 2014;Sasse et al, 2008;Watanasriyakul et al, 2018). Parts of the current study align well with these previously observed patterns.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Exercise is also known to activate the HPA axis and increase circulating glucocorticoid levels (Gerber et al, 2013;Hill et al, 2008;Skoluda et al, 2012;Tremblay et al, 2004). However, under conditions of chronic stress, exercise mitigates glucocorticoid levels and reduces depression-and anxiety-like behaviors (Campeau et al, 2010;Grippo et al, 2014;Sasse et al, 2008;Watanasriyakul et al, 2018). Parts of the current study align well with these previously observed patterns.…”
Section: Discussionsupporting
confidence: 87%
“…Experimental animals in the isolated groups were housed individually, without olfactory, auditory, or visual cues from the previous sibling. Previous work with this species has demonstrated that this duration of isolation is sufficient to induce behavioral and physiological consequences Grippo et al, 2008;McNeal et al, 2014;Peuler et al, 2012), and that access to exercise can mitigate these effects (Watanasriyakul et al, 2018). At the end of the five-week stressor period, a second hair sample was collected from each experimental animal, plasma samples were collected, and adrenal and body weights were recorded.…”
Section: Study Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…Using a chronic mild stress model, Watanasriyakul et al, (183) active" people were less likely to have SI but also were protected against SI.…”
Section: Major Depressive Disordermentioning
confidence: 99%